The Parent Cyclopentadienyltin Cation, Its Toluene Adduct, and the Quadruple‐Decker [Sn3Cp4]2+. (8th February 2017) - Schleep, Mario; Hettich, Clarissa; Velázquez Rojas, Jennifer; Kratzert, Daniel; Ludwig, Thilo; Lieberth, Katharina; Krossing, Ingo
Abstract: Truly cationic metallocenes with the parent cyclopentadienyl ligand are so far unknown for the Group 14 elements. Herein we report on an almost "naked" [SnCp] + cation with the weakly coordinating [AlOC(CF3 )3 4 ] − and [(F3 C)3 CO3 Al−F−AlOC(CF3 )3 3 ] − anions. [SnCp][AlOC(CF3 )3 4 ] was used to prepare the first main‐group quadruple‐decker cation [Sn3 Cp4 ] 2+ again as the [AlOC(CF3 )3 4 ] − salt. Additionally, the toluene adduct [CpSn(C7 H8 )][AlOC(CF3 )3 4 ] was obtained.